2013
DOI: 10.1152/ajpendo.00289.2013
|View full text |Cite
|
Sign up to set email alerts
|

Local NOS inhibition impairs vascular and metabolic actions of insulin in rat hindleg muscle in vivo

Abstract: Bradley EA, Richards SM, Keske MA, Rattigan S. Local NOS inhibition impairs vascular and metabolic actions of insulin in rat hindleg muscle in vivo. Am J Physiol Endocrinol Metab 305: E745-E750, 2013. First published July 30, 2013 doi:10.1152/ajpendo.00289.2013.-Insulin stimulates microvascular recruitment in skeletal muscle, and this vascular action augments muscle glucose disposal by ϳ40%. The aim of the current study was to determine the contribution of local nitric oxide synthase (NOS) to the vascular act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 42 publications
(58 reference statements)
1
39
0
Order By: Relevance
“…We have shown that acute defects in insulin-mediated microvascular recruitment can contribute to the development of muscle insulin resistance in vivo. Infusion of α-methyl serotonin [26], endothelin-1 [27], L-N G -Nitroarginine methyl ester [7,29,37], TNFα [38], Intralipid® plus heparin [39] and glucosamine [40] in healthy animals attenuate insulin-mediated microvascular recruitment and insulin-mediated muscle glucose uptake. In addition, chronic models of insulin resistance including the high fat-fed rat (36% fat wt/ wt) [3], and obese Zucker rat [41] display marked attenuation in insulin-mediated microvascular recruitment and muscle glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that acute defects in insulin-mediated microvascular recruitment can contribute to the development of muscle insulin resistance in vivo. Infusion of α-methyl serotonin [26], endothelin-1 [27], L-N G -Nitroarginine methyl ester [7,29,37], TNFα [38], Intralipid® plus heparin [39] and glucosamine [40] in healthy animals attenuate insulin-mediated microvascular recruitment and insulin-mediated muscle glucose uptake. In addition, chronic models of insulin resistance including the high fat-fed rat (36% fat wt/ wt) [3], and obese Zucker rat [41] display marked attenuation in insulin-mediated microvascular recruitment and muscle glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the concentrations of insulin required to cause an increased microvascular blood flow are lower than those required to increase whole-limb blood flow [26]. The role of bioavailable NO in skeletal muscle glucose uptake has been further clarified [53]. Recently, an investigative group has infused an eNOS inhibitor in the hind leg of anesthetized rats fed a regular diet [53].…”
Section: Effects Of Insulin On the Skeletal Muscle Vasculaturementioning
confidence: 99%
“…The role of bioavailable NO in skeletal muscle glucose uptake has been further clarified [53]. Recently, an investigative group has infused an eNOS inhibitor in the hind leg of anesthetized rats fed a regular diet [53]. No changes were reported in blood pressure or heart rate, but eNOS inhibition significantly blunted the insulin-stimulated increase of ultrasound-assessed femoral blood flow [53].…”
Section: Effects Of Insulin On the Skeletal Muscle Vasculaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, aging and insulin resistance are associated with reduced skeletal muscle capillary density, impaired endothelial function, and reduced nitric oxide (NO) availability (14,20,32,39,40). As such, age-related impairments in vascular function due to an impaired NO-mediated vasodilatory response and decreased muscle tissue perfusion may diminish feeding-mediated increases in muscle protein synthesis and, thus, contribute to the anabolic resistance of aging (7,24).It has been reported that dietary nitrate (NO 3 Ϫ ) supplementation, via sequential reduction of NO 3 Ϫ to nitrite (NO 2 Ϫ ) and NO, can stimulate NO synthesis and increase NO bioavailability (55). Moreover, it has been suggested that NO has a role in promoting insulin delivery to skeletal muscle tissue and increasing insulin-stimulated muscle perfusion and capillary action (22, 51).…”
mentioning
confidence: 99%